Изучение музыкальной природы художественного текста и его визуальных характеристик - Мирошниченко, Мария Павловна (Yolnat PE, 2021)
Действительность отражается в художественном тексте (текст понимается широко – как музыкальное, визуальное, вербальное и т.д. произведение), в соответствии с двумя принципами отражения: принципом проективности (сходство с реальностью проявляется на уровне конкретного образа, например, в реалистической живописи) и принципом концептуальности (сходство с реальностью наблюдается на уровне осмысления). Любой вербальный текст относится к текстам по преимуществу концептуального типа. К элементам проекции в таких текстах могут быть отнесены звукопись, расположение текста в виде картинки и т.п. Однако факт большей отдаленности конкретных образов вербального текста (которые формируют её реалистичность, детализированность, объёмность, экспрессивность и выразительность, т.е. материю текста) от исходного замысла автора, не может быть причиной отказа от анализа своеобразия материальной природы текста как одного из существенных признаков идиостиля. Кроме того, вербальному тексту присущи такие элементы фактической материи, как ритм, интонационные конструкции, повторы, аллитерации, апеллирующие к музыкальности произведения.

The reality is reflected in the artistic text according to two principles of reflection: the principle of projectivity (the similarity to reality is shown at the level of a concrete image, for example, in realistic painting or in a photo) and the principle of conceptuality (the similarity to reality is observed at the level of understanding, of connections between images). Any verbal text refers to texts predominantly of a conceptual type. The elements of projection in such texts can include sound writing, the location of the text in the shape of a picture, etc. However, the fact of greater remoteness of concrete images of the verbal text from the original intention of the author cannot be a reason for refusing to analyze the uniqueness of the material nature of the text as one of the essential features of an author`s writing style. The article examines the musical nature of the verbal text, as well as its pictorial features as a manifestation of secondary projectivity. The elements of textual reality that makes pictorial features include: attention to physical shape, to the description of appearance and external manifestations, documentary presentation, realistic, detailed, three-dimensional presentation, as well as a system of contrasts and figures of speech that impart expressiveness to the artistic world. In addition, such elements of factual matter as rhythm, intonation constructions, repetitions, alliterations, which appeal to the musicality of the work, are inherent in the verbal text. The study of the elements of material nature of the text allows to form a comprehensive idea of the texture of the artistic world of the work and to reveal due to what in particular the texture of the text or the author's writing style is formed.
Studying the musical nature of the artistic text and its visual characteristics
Keywords: материя текста; проективность; бытийность; экспрессивность; идиостиль; projectivity; matter of text; beingness; expressiveness; author's writing style